2019
DOI: 10.1038/s41419-019-1475-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Intracellular citrate accumulation by oxidized ATM-mediated metabolism reprogramming via PFKP and CS enhances hypoxic breast cancer cell invasion and metastasis

Abstract: Citrate, a substance being related to de novo fatty acid synthesis and tricarboxylic acid (TCA) cycle, has a pivotal role in cell survival. However, the molecular mechanisms that regulate intracellular citrate in triple-negative breast cancer (TNBC), especially under hypoxic condition, remain poorly understood. Here we find that hypoxia (1% O 2 ) induces DNA damage-independent ATM activation (oxidized ATM) and suppression of oxidized ATM reduces intracellular citrate via decreasing the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 50 publications
6
56
0
Order By: Relevance
“…Ubiquitination of enzymes involved in the TCA cycle is also associated with cancer progression. Decreased UBR5-mediated ubiquitination of citrate synthase leads to citrate accumulation in hypoxia breast cancer cells, promoting cell migration, invasion, and metastasis [269]. HIF-1 activation under hypoxia condition can promote α-ketoglutarate dehydrogenase (α-KGDH) complex ubiquitination and proteolysis by SIAH2.…”
Section: Ubiquitination and Metabolic Enzymesmentioning
confidence: 99%
“…Ubiquitination of enzymes involved in the TCA cycle is also associated with cancer progression. Decreased UBR5-mediated ubiquitination of citrate synthase leads to citrate accumulation in hypoxia breast cancer cells, promoting cell migration, invasion, and metastasis [269]. HIF-1 activation under hypoxia condition can promote α-ketoglutarate dehydrogenase (α-KGDH) complex ubiquitination and proteolysis by SIAH2.…”
Section: Ubiquitination and Metabolic Enzymesmentioning
confidence: 99%
“…This way, glucose is mainly metabolized in biosynthetic pathways, leaving the bioenergetics role to be played by glutamine. Moreover, citrate synthase (CS) expression is upregulated in cancer upon metabolic stressful conditions such as hypoxia, favoring the metabolic glutamine reliance [ 71 ]. Glutamine is also important in biomass production through the above-mentioned intervention in amino acid synthesis and also as a source for lipids, since citrate and glutamine-originated acetyl-CoA is the most relevant lipid precursor [ 63 , 72 , 73 ], accounting for about 20% of lipogenic acetyl-CoA [ 72 ].…”
Section: Glutamine-glutamate Relevance In Cancermentioning
confidence: 99%
“…Breast cancer is characterized by high PFKP expression that, in turn, has been associated with decreased patient survival [6]. Accumulating evidence has demonstrated that PFKP plays a crucial role in promoting aerobic glycolysis and lactate production in breast cancer cells, thereby stimulating cancer cell proliferation and metastasis [7][8]. Deletion of PFKP can signi cantly inhibit lactate production to impair invasion and migration by breast cancer cells [9,10].…”
Section: Introductionmentioning
confidence: 99%